Mandate performance reporting of Malaysian development financial institutions (DFIs): A review - Shamsudin, Norazidah; Mohammed, Mustafa Omar; Abd. Rahman, Nur Hasnida; Mustaffa Kamil, Nazrol Kamil (Asian Scholars Network, 2020)
Mandate is a source of power which give authority to organization in performing a task. For an organization who received mandate, it will affect their direction setting for which they will integrate in the firm’s vision or mission. Most of the organization who carries mandate would communicate the mandate received but some would not have a clear reporting on their mandated achievement. Hence, this study observed on mandate performance reporting by referring the recent published annual report of six Malaysian DFIs which under the purview of DFIA 2002. The objectives of the study are (1) to identify which of the DFIs have reported clearly their mandated achievement; (2) to investigate what are the dimensions, items and measures been utilized in the mandate reporting; and (3) to differentiate variation in mandate performance reporting framework between the DFIs. The findings would benefit the reader by providing information on the current mandated performance reporting practice of DFIs which also reflect their focus and strategic direction as a mandate executer.